Analisis Penyelesaian Perselisihan Hubungan Industrial di LuarPengadilan Melalui Arbitrase ( Studi Kasus Pada PT Agro Sinergi Nusantara, Kebun Tanoh Makmue Kecamatan Woyla Barat) - Siti Rakibah (Indo Publishing, 2025)
This study analyzes the effectiveness of industrial relations dispute resolution at PT Agro Sinergi Nusantara through out-of-court arbitration. Arbitration is considered effective in resolving disputes due to its faster process and lower costs compared to court proceedings. However, the success of arbitration is also influenced by the willingness of both parties to accept the decision. This study used qualitative methods with in-depth interviews and document analysis to understand the dynamics of dispute resolution at this company.